The unexpected diagnosis of karyomegalic interstitial nephritis in a presumed case of Mesoamerican Nephropathy: a case report - Kwon, Lawrence; Griffiths, Jennifer; DiFranza, Lanny T. (Frontiers in Medicine, 2025)
BackgroundChronic kidney disease of unknown etiology (CKDu) is a form of chronic kidney disease commonly found in certain rural populations globally. This condition is characterized by chronic tubulointerstitial nephropathy, yet it lacks specific signature lesions and is believed to have a multifactorial etiology, often associated with environmental toxins. Karyomegalic Interstitial Nephritis (KIN), although a rare form of chronic interstitial nephropathy leading to end-stage kidney disease, is not classified under CKDu.Case presentationIn this case report, we explore the diagnostic journey of a 40-year-old male farmer from Guatemala. He presented with headache, fever, and facial pain, but laboratory tests revealed significant kidney impairment and liver dysfunction. The pivotal point in his diagnostic workup was a kidney biopsy, which showed severe chronic tubulointerstitial scarring and enlarged, hyperchromatic nuclei in the tubular epithelial cells, confirming KIN. This diagnosis marked a departure from the initial suspicion of Mesoamerican Nephropathy (MEN).ConclusionThis case underscores the critical need for a comprehensive evaluation in atypical presentations of chronic kidney disease, particularly emphasizing the importance of being vigilant for KIN in areas where MEN is commonly diagnosed.